REPRESENTATION OF EXISTENTIALIST FEMINISM IN “SUFFRAGETTE” MOVIE SCRIPT - Yuhendra Yuhendra; Nofrika Sari; Rika Andriani; Afdaleni Afdaleni; Albert Albert; Haris Syukri; Dewi Ade Putri (Jurnal Kata, 2026)
This research examines the representation of existentialist feminism in Abi Morgan’s script for the film Suffragette. While previous studies on the film primarily discuss historical or broad socio-political paradigms, this research highlights its novelty by exploring how female characters actively subvert their status as "the Other" through textually recorded dialogue and narrative choices. Drawing on Simone de Beauvoir’s existentialist feminist framework-specifically her critiques of biology, psychoanalysis, historical materialism, and patriarchal myths and integrating contemporary lenses from Judith Butler’s gender performativity and intersectionality, this qualitative study employs close reading and descriptive-analytic methods to dissect the script. The findings reveal that while patriarchal structures attempt to lock women into a state of oppressive immanence (through workplace exploitation, institutionalized sexual harassment, and legal dispossession), the characters achieve existentialist transcendence. By executing deliberate, performative acts of resistance, the working-class women of the suffrage movement reclaim their subjectivity, shifting from passive objects to self-defined, autonomous existential agents.